Long term impact of the WHI studies on information-seeking and decision-making in menopause symptoms management: a longitudinal analysis of questions to a medicines call centre - Rifani B. Natari; Samantha A. Hollingworth; Alexandra M. Clavarino; Kaeleen D. Dingle; Treasure M. McGuire (BMC, 2021)
Abstract Background While women are taking a greater role in decisions about menopause symptom management, the legacy of the Women's Health Initiative (WHI) studies persist. Despite hormone therapy (HT) being effective in reducing all-cause mortality, many women seeking relief of menopausal symptoms exaggerate HT harms and overstate the perceived benefits or ignore the risks of alternative therapies. We aimed to explore the longitudinal impact of the widely-publicised WHI 2002 study on women's information-seeking and describe determinants of decision-making about managing menopausal symptoms. Methods In a longitudinal analysis of both quantitative and qualitative data, we explored consumer questions about menopause-related medicines received by two Australian medicines call centres (1996-2010) before, during, and after WHI 2002. We analysed calls by age and gender of caller and patient, their relationship, postcode, enquiry type, and motivation to help-seek. We compared calls regarding HT and herbal medicines (HM) with the rest of calls, and thematically analysed question narratives across the three time-periods. Results There were 1,829 menopause-related calls received of over this time-period, with a call surge, primarily from women in their mid-fifties, in the two months after the WHI 2002 publication. Two in three calls were motivated by negative media reports as women sought support for decision-making, primarily reassurance to cease HT. While HT safety concerns persisted for eight years post-publication, the nature of information-seeking changed over time. Callers subsequently sought reassurance to use menopause treatments together with their other medicines; and pursued HT substitutes, including HM, in response to HT product discontinuation. Conclusions Women sought information or reassurance to support a decision, based on dynamic changes in internal (symptom or risk intolerance, attitude towards menopause and treatment preferences) and external factors (perceived source trust and changes in treatment availability). In assessing HT benefit versus risk, women tend to overestimate risk with HT safety concerns persisting over time. Decision-making in managing menopause symptoms is complex and dynamic. Reassurance to reach or justify decisions from a perceived trusted source can support informed decision-making.